THE EFFECT OF LEARNING STRATEGY AND INITIAL KNOWLEDGE ON THE ABILITY TO DEVELOP WRITING SKILLS ASSESSMENT INSTRUMENTS - Edi Puryanto; Yumna Rasyid; Fathiathy Murtadho (English Education Department, 2020)
This study was aimed at identifying the the effect of learning strategies and initial knowledge on the ability in developing writing skills assessment instruments for students in the Indonesian Language and Literature Education Study Program, FBS, UNJ. The method used in this research was experimental research with 46 samples. Sample 3 PB1 was treated with metacognition strategy and sample 3 PB2 was treated, with strategy advance organizer. The research instrument was a test of the ability to develop writing skills assessment instruments and a test of initial knowledge. After testing the hypothesis with the ANOVA test, in the 2 X 2 calculation table, Fcount (Inter-A) 6.008> Ftable 4.200 at the level of α = 0.05, indicating that H1 is accepted and Ho is rejected. This means that there are differences in ability to develop writing skills assessment instruments between students who are treated with metacognition strategies and strategies advance organizer. Furthermore, testing the hypothesis about the effect of the interaction of learning strategies and initial knowledge on the ability to develop writing skills assessment instruments and testing prior knowledge, data shows arithmetic (AxB interaction) = 5.485> ftable = 4,200 on the level of α = 0.05, H1 accepted and Ho rejected. That is, there is an interaction effect between learning strategies (metacognition strategies and strategies advance organizer) and initial knowledge (high and low) on the ability to develop writing assessment skills instruments. The learning outcomes of the ability to develop students' writing assessment skills instruments are influenced by learning strategies and initial knowledge.